Factors Affecting Consumers’ Recycling Behavior in Developing Countries: Extending the Theory of Planned Behavior in the Recycling Domain (KASBIT Business Journal, 2022)
This study examines the factors that may influence recycling behavior of consumers in developing countries, specifically in the context of Pakistan. A conceptual framework was proposed using TPB to explain the impact of consumer knowledge and perceived consumer effectiveness on consumer recycling The respondents were selected by using non-probability sampling technique and the questionnaire was shared online with the respondents by using different digital platforms. The data was collected form 324 respondents living in Karachi, Pakistan and analyzed through Structure Equation Modeling on SMART PLS. The findings suggest that attitude, perceived consumer effectiveness and subjective norms show positive significant impact on consumers recycling intention. However, there is an insignificant impact of Consumer Knowledge and Perceived Behavior Control on recycling intention. The findings of the study are relevant for marketers, government/policymakers, businesses, manufacturers, environmentalists and academicians. This study would help practitioners and marketers in developing their strategy to promote recycling behavior in developing countries.
Keywords: Recycling Behavior; Theory of Planned Behavior; Perceived Consumer Effectiveness; Consumer Knowledge; Recycling Intention